2001
DOI: 10.1177/152660280100800611
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Secondary Aortoesophageal Fistula by Endoluminal Stent-Grafting

Abstract: Endoluminal repair can be successful in achieving a satisfactory midterm outcome in cases of secondary aortoesophageal fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Semba et al, 12 who treated mycotic descending thoracic aortic aneurysms with endovascular therapy, reported that infection may be controlled by aggressive antibiotic therapy as the sole adjunct to stent grafting. This approach should be used for specific indications such as infection with low‐virulence organisms, absence of gross purulence, and high‐operative risk 7 , 13 . Emergent endovascular repair in patients who present with bleeding, such as our patient, can accomplish an expedient repair without the morbidity of the open repair.…”
Section: Discussionmentioning
confidence: 99%
“…Semba et al, 12 who treated mycotic descending thoracic aortic aneurysms with endovascular therapy, reported that infection may be controlled by aggressive antibiotic therapy as the sole adjunct to stent grafting. This approach should be used for specific indications such as infection with low‐virulence organisms, absence of gross purulence, and high‐operative risk 7 , 13 . Emergent endovascular repair in patients who present with bleeding, such as our patient, can accomplish an expedient repair without the morbidity of the open repair.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience with the use of stent grafts in the management of aortoesophageal fistulae is limited to several recent case reports. 87,[89][90][91][92][93][94][95][96][97][98][99][100] Effective hemorrhage control can be rapidly established without the requirement for emergent thoracotomy. Used in this fashion, endoluminal devices may provide the opportunity to facilitate appropriate resuscitation and medical optimization, thereby functioning as a bridge.…”
Section: Role Of Endovascular Therapy In Management Of Aortoesophageal Fistulaementioning
confidence: 99%
“…Cautious use of endovascular grafts [3][4][5][6] and close postoperative monitoring may be helpful in avoiding the known complications of open surgery for aortoesophageal fistula. We selected an endovascular approach to avoid manip-ulation and possible disruption of the pseudoaneurysm, but also because we considered it more reasonable to place an endograft in the aorta rather than directly inside an abscess cavity.…”
Section: Stent-grafting Of An Infected Aortoesophageal Fistula Followmentioning
confidence: 99%